Leisure Life : Myth, Modernity And Masculinity. - Blackshaw, Tony (Taylor & Francis Ltd., 2003)
Leisure Life awakens the sociological imagination. It offers a new approach to the study of masculinity and the ethnography of leisure, making it appropriate for courses in sociology, leisure, cultural and gender studies.